“Horace for Marina Mnishek”: Heroes of Time of Troubles in Poetry by Sebastian Petritsi - N. V. Eylbart (Научный диалог, 2017)
The historical analysis of “Horatius Flaccus in the works of the Moscow prisoner” is made, the outstanding work of Polish Renaissance era, written by Dr Sebastian Petritsi - Professor of Krakow University and the doctor of the family of Marina Mnishek. Biographical information about the scientist’s life and the circumstances in which he had been staying in the Moscow state for a year and a half are covered. Political motives are characterized, based on which Petritsi translated the odes and epodes by Horace. On the one hand, this work had as propaganda and urged the Poles to start a war with Muscovite state. On the other hand, it once again “raised from the dead” the Tsar False Dmitry I killed by a boyar conspiracy and gave the reader hope that he still could be saved. Thirdly, the work had a psychological impact - stilled captive Polish aristocrats, who came to the wedding of Marina Mnishek. Attention is drawn to the fact that the first in the history of Slavic literature complete translation of the lyric works of Horace was carried out with the support of the family Mnishek and dedicated to them by the author. It is concluded that it can serve as a valuable historical source for the psychological characteristics of the Polish participants in the events of the Time of Troubles.